PERANCANGAN MEDIA INFORMASI PENUNJANG KESEHATAN IBU HAMIL BERBASIS MULTIMEDIA DENGAN METODE PENGUJIAN BLACK BOX - Herman Mulyana (LPPM Universitas Bina Sarana Informatika, 2014)
In the era of information technology and now this is where almost everyone has a computer, laptop or smart phone to make the wearer more closely with the technology compared to print media such as books and newspapers. The use of print media to convey information've felt less able to deliver to the general public. What's more, especially to the people that a lot of busyness and career. While there are some important things to be delivered, for example supporting maternal health information to pregnant women, especially pregnant mothers candidate's first child. The solution to overcome this is done this research is intended to design media information supporting multimedia-based maternal health. Multimedia is one right way to simplify the delivery of information in the form of visual and audio. The existence of multimedia has changed the way humans interact with computers and smart phones is through media images, text, audio, animation and video images that interact and integrate with each other. Submission information can be better due to the multimedia are capable of producing media becomes more interesting and lively. Black box testing is performed to determine the performance of applications and correspondence between inputs and outputs so that the data is displayed in accordance with the input data in the application view.